Clinical relevance of stress biomarkers as health-disease indicators - Morales-López, César A. (Mexican Journal of Medical Research ICSA, 2022)
Stress is a protective mechanism inherent in living organisms. In humans, it fulfils an adaptive function, capable of generating responses at different levels: physiological, metabolic, endocrine, cognitive, among others. Constant exposure to stressful events or stimuli is capable of exceeding the person’s resources, causing discomfort and progressively wearing down health. Recently, a significant increase in stress-associated diseases has been observed. The consequences of this problem are multiple; personal, socioeconomic, and professional difficulties. Current evidence shows that daily stress will tend to increase in the upcoming years, affecting the quality of life and mental health of the population in general. Both environmental and natural factors as well as the economic and social repercussions derived from the current pandemic tend to further aggravate this problem. Given this scenario, developing strategies that promote mental health and the prevention of its associated pathologies is a priority. One way to develop more effective intervention programs is through the use of biomarkers, many of which show high diagnostic sensitivity and specificity, and which represent a wide interest within the clinical area and psychotherapeutic intervention. The objective of this article is to make a general review of the main biomarkers used in clinical practice, as well as potential biomarkers that allow the identification of early signs of health problems related to mental stress in a more efficient and accessible way.